Microsoft dynamics CRM 2011 step by step - Snyder, Mike; Steger, Jim; Landers, Brendan (Step by step (Redmond, Wash.), 2011)
The smart way to learn Microsoft Dynamics CRM 2011—one step at a time! Use the easy-to-follow lessons to master the fundamentals of creating and managing accounts; working directly within familiar tools such as Microsoft Outlook; tracking customer activity and communications; managing campaigns, leads, quotes, contracts, and orders; and employing basic to advanced reporting capabilities. Includes downloadable, ready-made practice files and complete Book.